IMPAIRED LOAN: MUDHARABAH AND MUSYARAKAH FINANCING RISK ON RETURN ON EQUITY AT ISLAMIC COMMERCIAL BANKS FOR THE PERIOD 2014-2020 - Muhammad, Farrel Febrian; Noerzaeny, Ihsan; Dwijayanti , Rima; Perdana, Rangga Satria; Lusiana, Senny (PT. Altin Riset Publishing, 2024)
The purpose of this study is to determine the effect of Mudharabah and Musyarakah Financing Risks on Return on Equity at Islamic Commercial Banks for the 2014-2020 period. Research method Data analysis uses correlation and determination coefficient analysis and partial and simultaneous hypothesis testing. This research is categorized into descriptive and verification research. The data used in this study are secondary. Panel data testing which includes CEM, FEM, REM, Chow Test, Hausman Test, LM Test, Classical assumption tests includes Normality Test, Multicollinearity, Heteroscedasticity, and autocorrelation. Findings Based on the results of the research conducted, the result is that NPF Mudharabah partially affects Return On Equity. The value seen from the t-count is smaller than the t-table, namely - 2.552355 < -1.895 with a significance level of 0.0134 which is smaller than 0.05. NPF Musyarakah partially does not affect Return On Equity, as seen from the t-count which is smaller than the t-table, namely 1.082097 < -1.895 with a significance level of 0.2837 which is greater than 0.05. Simultaneously NPF Mudharabah and NPF Musyarakah affect Return On Equity. Judging from the probability, namely 0.0000, it is smaller than the alpha value (0.05) and the F-count is greater than the F-table, namely 8.350840> 4.74.